Epidemiological Investigation in Diphtheria Control in Banda Aceh, Indonesia - Aini, Zahratul; Pamungkasari, Eti Poncorini; Probandari, Ari Natalia (Journal of Epidemiology and Public Health, 2020)
Background: Extraordinary events (KLB) diph